Funktional awareness and yoga - Romita, A.; Romita, N. (Oxford University Press, 2019)
Functional Awareness and Yoga is an essential book for all who wishes to deepen their yoga practice and discover strategies to reduce strain or discomfort on the mat as well as in daily life. It is also an excellent book of introductory concepts in anatomy as applied to yoga required during a yoga teacher training. Each chapter provides essentials in functional anatomy with over 60 practical illustrations. The chapters also apply specific postures in yoga with cues to support the practice on the mat. Finally, each chapter contains a mindful practice section to help readers integrate anatomical imagery into daily life in order to release unnecessary tension, improve posture, and support ease of movement.